HBR's 10 must reads on building a great culture - Grant, Adam.; Groysberg, Boris; Katzenbach, Jon R.; Meyer, Erin.; Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2019)
"Your organization's culture can feel like something that has a life of its own; its long-standing, inherited, and seemingly impermeable--in fact, a strong culture is often an obstacle to doing new things or going in new directions. But leaders are the stewards of a company's culture and have the power to shape it. The best leaders know that organizational culture is a fundamental and powerful management tool that can drive positive outcomes. If you read nothing else on building a better organizational culture, read these 10 articles by experts in the field. We've combed through hundreds of articles in the Harvard Business Review archive and selected the most important ones to help you assess the type and current state of your company's culture, communicate change, do things differently, and anticipate and address implementation challenges. This book will inspire you to: determine what type of culture you have; understand the psychology behind your company's social patterns; gather input on what needs to be fixed or initiated; communicate change; do things differently; deal with implementation roadblocks"--
The leader's guide to corporate culture / by Boris Groysberg, Jeremiah Lee, Jesse Price, and J. Yo-Jud Cheng -- Manage your emotional culture / by Sigal Barsade and Olivia A. O'Neill -- The neuroscience of trust / by Paul J. Zak -- Creating a purpose- driven organization / by Robert E. Quinn and Anjan V. Thakor -- Creating the best workplace on earth / by Rob Goffee and Gareth Jones -- Cultural change that sticks / by Jon R. Katzenbach, Ilona Steffen, and Caroline Kronley -- Bonus article: How to build a culture of originality / by Adam Grant -- When culture doesn't translate / by Erin Meyer -- Culture is not the culprit / by Jay W. Lorsch and Emily Gandhi -- Conquering a culture of indecision / by Ram Charan -- Radical change, the quiet way / by Debra E. Meyerson.
"Bonus article "How to build a culture of originality" by Adam Grant"--Cover.
Includes index.
Print version record.
Keywords: Corporate culture; Leadership; elektronické knihy; electronic books